Evaluation of Ground‐Based and Helicopter Ground‐Penetrating Radar Data Acquired Across an Alpine Rock Glacier. (3rd February 2015) - Merz, Kaspar; Maurer, Hansruedi; Buchli, Thomas; Horstmeyer, Heinrich; Green, Alan G.; Springman, Sarah M.
Abstract To forecast rock glacier movements, it is necessary to have dependable information on their internal structures and physical properties. A first attempt to expand our knowledge of a rock glacier in the Swiss Alps involved acquiring ground‐based ground‐penetrating radar (GPR) data along numerous profiles using different acquisition systems and antennae with different nominal frequencies. Images derived from these ground‐based data were inconsistent and unreliable. For our second attempt, we recorded GPR data using a helicopter‐mounted system. The helicopter GPR sections were surprisingly good, with consistent images along adjacent and intersecting profiles. Internal shear horizons, ice‐rich and ice‐poor regions and the bedrock interface were well delineated on the helicopter GPR images. Besides providing excellent‐quality images, the helicopter GPR system allowed areas of the rock glacier to be surveyed that would have been difficult or impossible to access for a ground‐based study. Because near‐surface heterogeneity does not seem to have a major effect on helicopter GPR data acquired across a rugged rock glacier, we suggest that helicopter GPR surveying might be useful for investigating many terrains covered by heterogeneous loose material, including debris avalanches, scree slopes and rockfalls. Copyright © 2015 John Wiley & Sons, Ltd.